PEMODELAN PETA TOPOGRAFI KE OBJEK TIGA DIMENSI - Rostianingsih, Silvia; Handoyo, Ivan; Gunadi, Kartika (Institute of Research and Community Outreach - Petra Christian University, 2004)
A topography map is a map which have an information about surface of the land height at a place from the surface of the sea, that drawn with topography's lines. Topography information in topography map can be used to create three dimensions model of this map's surface. With this three dimension model, an object at the map can be seen more live as in the real world, and because of that to analyze a topography map could be done easier. Abstract in Bahasa Indonesia : Peta topografi adalah peta yang memiliki informasi tentang ketinggian permukaan tanah pada suatu tempat terhadap permukaan laut, yang digambarkan dengan garis-garis kontur. Informasi topografi yang terdapat pada peta topografi dapat digunakan untuk membuat model tiga dimensi dari permukaan tanah pada peta tersebut. Dengan model tiga dimensi maka objek pada peta dilihat lebih hidup seperti pada keadaan sesungguhnya di alam, sehingga untuk menganalisa suatu peta topografi dapat lebih mudah dilakukan. Kata kunci: Peta, Topografi, Geografi, Tiga Dimensi.